Justified. City primeval. Season 1 [videorecording (DVD)] - Andron, Dave; Dinner, Michael (Sony Pictures Home Entertainment, 2023)
Having left the hollers of Kentucky 15 years ago, Raylan Givens now lives in Miami, a walking anachronism balancing his life as a U.S. Marshal and part-time father of a 15-year-old girl. His hair is grayer, his hat is dirtier, and the road in front of him is suddenly a lot shorter than the road behind. A chance encounter on a desolate Florida highway sends him to Detroit. There he crosses paths with Clement Mansell, aka The Oklahoma Wildman, a violent, sociopathic desperado who's already slipped through the fingers of Detroit's finest once and aims to do so again. Mansell's attorney, formidable Motor City native Carolyn Wilder, has every intention of representing her client, even as she finds herself caught between cop and criminal, with her own game afoot as well. These three characters set out on a collision course in classic Elmore Leonard fashion, to see who makes it out of the City Primeval alive.